2016
DOI: 10.1097/md.0000000000003891
|View full text |Cite|
|
Sign up to set email alerts
|

Prolonged hemidiaphragmatic paresis following continuous interscalene brachial plexus block

Abstract: Interscalene brachial plexus block provides effective anesthesia and analgesia for shoulder surgery. One of the disadvantages of this technique is the risk of hemidiaphragmatic paresis, which can occur as a result of phrenic nerve block and can cause a decrease in the pulmonary function, limiting the use of the block in patients with reduced functional residual capacity or a preexisting pulmonary disease. However, it is generally transient and is resolved over the duration of the local anesthetic's action.We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…In this context, comparative anatomy of the formation of the brachial plexus has been studied since the 19th century (Paterson 1887). The brachial plexus is a complex anatomical structure, from its origin to the neck and to its final branching in the axillary region (Fazan et al 2003), and remains one of the most intriguing themes of contemporary anatomy (Johnson et al 2010;Souza-Junior et al 2014;Mistry et al 2016;Shinn et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, comparative anatomy of the formation of the brachial plexus has been studied since the 19th century (Paterson 1887). The brachial plexus is a complex anatomical structure, from its origin to the neck and to its final branching in the axillary region (Fazan et al 2003), and remains one of the most intriguing themes of contemporary anatomy (Johnson et al 2010;Souza-Junior et al 2014;Mistry et al 2016;Shinn et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the anatomical characteristics and the variations of this plexus is an important ally in applied studies, and may make the diagnosis of neuromuscular dysfunctions easier (Freeman et al 2009). Besides, it may guide local and regional anaesthetic nerve block techniques, once these techniques lead to intraoperative analgesia for musculoskeletal structures of the thoracic limbs and the shoulders (Futema et al 1999;Mencalha et al 2014Mencalha et al , 2016Mistry et al 2016;Shinn et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Once these conditions occur, surgeons need to consider the possibility of thoracotomy and the possibility of stopping the study at any time. A fall in blood pressure is known to occur during propofol-based anaesthesia 21 , and PNB has a transient effect on pulmonary function that is limited to the duration of the operation 22 , 23 . In the present study, all of these factors were indeed observed in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the anatomic pattern and potential variations in the development of the brachial plexus is important in specific situations. For example, it can guide local and regional anaesthetic blocking techniques that result in the analgesia of somatic structures in thoracic limbs (Futema et al 1999;Mencalha et al 2016;Mistry et al 2016;Shinn et al 2016).…”
Section: Introductionmentioning
confidence: 99%